"Deutsch, deutsch!" - Čuček, Filip (Časopis za zgodovino in narodopisje, 2021)
In this piece, the author analyses the performance of Fran Rosina, a Lower-Styrian member of the parliament and Ljutomer/Maribor attorney, in the regional parliament during his only mandate (1869-1902). The establishment of the Slovene parallels in Celje in the year 1895 caused negative reactions amongst all German nationals in the monarchy, and subsequently forced the Windischgrätz government to resign. After Badeni's language decrees in 1897, which caused fierce German feedback, the Lower-Styrian Germans, with no exceptions firmly and strongly responded to the Slovene actions. At the turn of the century, conflicts between Germans and Slovenians were present on every corner, and the German side had a much better starting point in the national battle, which they also made good use of. As a Slovenian member of the regional parliament in Graz, Rosina was also involved in this fierce international battle. In 1895 he moved to Ljutomer, and became a member of the regional parliament the following year; in 1900 he decided to withdraw, together with the rest of the Slovenian members of the parliament, and in 1902, the year of the new elections, decided not to run for the parliament again.
Keywords: 19.st.; deželni zbori; etnični konflikti; Gradec; narodnostno vprašanje; Rosina, Fran; slovenski odvetniki; slovenski politiki; Spodnja Štajerska